Amidoxime modified LDH-O-PA two-dimensional nanosheet array electrode material and preparation method and application thereof
Through electrochemical synthesis and PAN coating technology, the morphology and reactive oxygen exposure of LDHs nanosheets were regulated, and LDH-O@PA two-dimensional nanosheet array electrode material with high surface area and dispersion stability was prepared, solving the existing solutions The problem of large energy consumption of nanomaterial preparation in the technology has achieved efficient adsorption of heavy metal ions and the application of seawater uranium extraction.
Patent Information
- Application Number
- CN202411351779.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-26
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2044-09-26
AI Technical Summary
Existing nanomaterial preparation methods such as liquid phase hydrothermal method require high temperature and high pressure, resulting in high energy consumption and strict equipment requirements, and it is difficult to achieve rapid preparation of new nanomaterials at low voltage.
By electrochemical synthesis method, LDHs structured electrodes were constructed on the conductive substrate through the regulation of constant potential time and voltage magnesium, and activated by cyclic voltammetry, combined with the coating of PAN and DMF, amidoxime modified amidoxime was prepared. LDH-O@PA two-dimensional nanosheet array electrode material.
The nanosheet size and density control are achieved, the excellent morphology of the material is maintained, the active site utilization rate of the electrode material is improved, the surface area and dispersion stability are enhanced, and the synergistic adsorption effect on heavy metal ions is good. , suitable for seawater uranium extraction and nuclear wastewater treatment.
Smart Images

Figure CN119194486A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of inorganic nanomaterial synthesis, and particularly relates to an amidoxime-modified LDH-O@PA two-dimensional nanosheet array electrode material, a preparation method and an application thereof. Background Art
[0002] In the prior art, the preparation of nanomaterials mostly uses liquid phase hydrothermal method. The structure and morphology of the materials obtained by this preparation method are relatively controllable, so it is widely favored by researchers or enterprises. However, the hydrothermal method generally requires high temperature and high pressure, which leads to serious energy consumption in the production process and more stringent requirements on equipment. Electrochemical synthesis is a new convenient and feasible method for rapid preparation of nanomaterials on conductive substrates. By regulating the composition, pH, temperature and synthesis voltage of the electrolyte solution, it is expected to obtain a method for rapid preparation of new nanomaterials at low voltage.
[0003] Layered double hydroxides (LDHs, also known as hydrotalcites) are a low-cost, non-toxic, highly thermally stable and environmentally friendly inorganic layered material with a wide range of applications. Due to the fact that the types, proportions and distribution of divalent and trivalent metal ions in the main layer and the interlayer guests can be artificially controlled, and the diversity of its design, synthesis and assembly, the exchangeable interlayer anions and the variable valence of metal ions in the layer, the composition or structure of LDHs can be regulated or modified according to different requirements such as use and performance, to obtain LDHs materials that meet different needs. Summary of the invention
[0004] The purpose of the present invention is to provide a preparation method and use of an amidoxime-modified LDH-O@PA two-dimensional nanosheet array electrode material, and provide a new method for synthesizing nanosheet arrays by a one-step electrosynthesis method. The degree of oxygen exposure in the target compound can be adjusted by regulating the constant potential time and voltage, so that the product has a larger surface area and dispersion stability, and has a good synergistic adsorption effect on heavy metal ions.
[0005] To achieve the above object, the present invention provides a method for preparing an amidoxime-modified LDH-O@PA two-dimensional nanosheet array electrode material, comprising the following steps:
[0006] S1. Construction of LDHs structured electrode: prepare a mixed solution of soluble metal nitrate and sulfate as an electrolyte solution, a saturated calomel electrode as a reference electrode, Pt as a counter electrode, select a clean conductive substrate for constant potential deposition, and directly grow an LDHs nanosheet array on the conductive substrate to obtain an LDHs structured electrode. The LDHs structured electrode is dried at 60° C. for 6 hours and then stored;
[0007] S2. Construction of LDH-O electrode: Using cyclic voltammetry, the LDHs structured electrode is electrochemically activated in a KOH solution to obtain an LDH-O electrode;
[0008] S3, LDH-O@PA two-dimensional nanosheet array electrode material construction: PAN and DMF were mixed and stirred at a mass ratio of 1:30 for 10-15h, the LDH-O electrode was soaked in it, and it was suspended and dried at 70°C; 25mL of a solution containing hydroxylamine hydrochloride and Na2CO3 was prepared with deionized water, the dried LDH-O electrode was soaked in it, and it was placed in a water bath at 70°C for 90min. After washing with deionized water, it was air-dried at 80°C in a drying oven to obtain the LDH-O@PA two-dimensional nanosheet array electrode material.
[0009] Preferably, in step S1, the conductive substrate is selected from any one of nickel foam, ITO, FTO, nickel sheet, titanium sheet, copper mesh, carbon fiber cloth and transparent conductive cloth.
[0010] Preferably, the cleaning method of the conductive substrate is: ultrasonically treat the conductive substrate with anhydrous ethanol, acetone and deionized water for 10-20 minutes respectively to remove impurities on the surface, and then soak it in a standard potassium permanganate solution for 10 hours.
[0011] Preferably, the soluble metal nitrate is selected from any one of Mg(NO3)2, Co(NO3)2, Ni(NO3)2, Ca(NO3)2, Cu(NO3)2, Fe(NO3)2, Mn(NO3)2, and LiNO3; the sulfate is FeSO4·7H2O, the molar ratio of the soluble metal nitrate to the sulfate in the mixed solution is (2:1)-(1:2), the concentration of the soluble metal nitrate is 0.1-1.5 mg / mL, and the concentration of the divalent iron sulfate is 0.1-1.5 mg / mL.
[0012] Preferably, in step S1, the SCE potential of the conductive substrate is -2 to -0.5 V, the time of the constant potential deposition is 50-400 s, and the temperature of the constant potential deposition is 10-50°C.
[0013] Preferably, in step S2, the concentration of the KOH solution is 0.1 M, and the cyclic voltammetry potential is 1-4 V vs SCE.
[0014] Preferably, in step S3, the LDH-O electrode is immersed for 30-90 minutes.
[0015] Preferably, in step S3, in the mixed solution of hydroxylamine hydrochloride and Na2CO3, the concentrations of hydroxylamine hydrochloride and Na2CO3 are 80 mg / mL and 60 mg / mL, respectively.
[0016] The present invention also provides an amidoxime-modified LDH-O@PA two-dimensional nanosheet array electrode material, which is prepared from the above-mentioned amidoxime-modified LDH-O@PA two-dimensional nanosheet array electrode material.
[0017] The amidoxime-modified LDH-O@PA two-dimensional nanosheet array electrode material provided by the present invention is applied in the fields of uranium extraction from seawater and nuclear wastewater treatment.
[0018] Therefore, the present invention adopts the above-mentioned amidoxime-modified LDH-O@PA two-dimensional nanosheet array electrode material and its preparation method and application, and its beneficial effects are:
[0019] (1) The present invention regulates the size and density of hydrotalcite nanosheets by regulating the electrosynthesis time to achieve optimal performance. The material prepared based on this method can not only maintain the excellent morphology of the LDHs precursor to a great extent and achieve a high utilization rate of the active sites of the electrode material, but also achieve dehydrogenation reconstruction on the surface of LDHs through a constant potential oxidation process to expose active oxygen groups (LDH-O). The degree of oxygen exposure in the target compound can be adjusted by regulating the constant potential time and voltage, thereby achieving fine regulation of the microstructure of the electrode material.
[0020] (2) The present invention adopts a simple and rapid one-step electrosynthesis method for the first time to prepare LDH nanosheet arrays on a conductive substrate, and modify them to obtain LDHs with good hydrophilicity; the LDHs composite nanomaterials have a high surface area and abundant binding sites, so that the electron-rich groups (amines and imines) on the polymer chain produce electrostatic interactions with LDHs, thereby preventing the stacking characteristics of LDHs sheets. LDHs nanocomposite materials usually have a large surface area and dispersion stability, and have a good synergistic adsorption effect on heavy metal ions. The synthesized transition metal-based two-dimensional structured electrode materials have a very broad application prospect in the field of uranium extraction from seawater.
[0021] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 This is a flow chart for preparing an amidoxime-modified LDH-O@PA two-dimensional nanosheet array electrode material of the present invention;
[0023] Figure 2 This is a scanning electron microscope image of the CoFe-LDH nanosheet array prepared in Example 1 of the present invention;
[0024] Figure 3 This is a scanning electron microscope image of the CoFe-O nanosheet array prepared in Example 1 of the present invention;
[0025] Figure 4 This is a scanning electron microscope image of the LDH-O@PA nanosheet array prepared in Example 1 of the present invention;
[0026] Figure 5 This is a scanning electron microscope image of the LDH-O@PA nanosheet array prepared in Example 1 of the present invention after adsorbing uranium. DETAILED DESCRIPTION
[0027] The technical solution of the present invention is further described below through the accompanying drawings and embodiments.
[0028] Unless otherwise defined, technical or scientific terms used in the present invention shall have the common meanings understood by one having ordinary skills in the field to which the present invention belongs.
[0029] In addition, it should be understood that although this specification is described in accordance with the implementation modes, not every implementation mode includes only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment can also be appropriately combined to form other implementation modes that can be understood by those skilled in the art. These other implementation modes are also covered within the protection scope of the present invention.
[0030] As attached Figure 1 As shown in the flowchart shown, the present invention provides a method for preparing an amidoxime-modified LDH-O@PA two-dimensional nanosheet array electrode material, comprising the following steps:
[0031] S1. Construction of LDHs structured electrode: prepare a mixed solution of soluble metal nitrate and sulfate as an electrolyte solution, a saturated calomel electrode as a reference electrode, Pt as a counter electrode, select a clean conductive substrate for constant potential deposition, and directly grow an LDHs nanosheet array on the conductive substrate to obtain an LDHs structured electrode. The LDHs structured electrode is dried at 60° C. for 6 hours and then stored;
[0032] S2. Construction of LDH-O electrode: Using cyclic voltammetry, the LDHs structured electrode is electrochemically activated in a KOH solution to obtain an LDH-O electrode;
[0033] S3, LDH-O@PA two-dimensional nanosheet array electrode material construction: PAN and DMF were mixed and stirred at a mass ratio of 1:30 for 10-15h, the LDH-O electrode was soaked in it, and it was suspended and dried at 70°C; 25mL of a solution containing hydroxylamine hydrochloride and Na2CO3 was prepared with deionized water, the dried LDH-O electrode was soaked in it, and it was placed in a water bath at 70°C for 90min. After washing with deionized water, it was air-dried at 80°C in a drying oven to obtain the LDH-O@PA two-dimensional nanosheet array electrode material.
[0034] In step S1, the conductive substrate is selected from any one of nickel foam, ITO, FTO, nickel sheet, titanium sheet, copper mesh, carbon fiber cloth and transparent conductive cloth.
[0035] The cleaning method of the conductive substrate is as follows: ultrasonically treat the conductive substrate with anhydrous ethanol, acetone and deionized water for 10-20 minutes respectively to remove impurities on the surface, and then soak it in a standard potassium permanganate solution for 10 hours.
[0036] The soluble metal nitrate is selected from any one of Mg(NO3)2, Co(NO3)2, Ni(NO3)2, Ca(NO3)2, Cu(NO3)2, Fe(NO3)2, Mn(NO3)2, and LiNO3; the sulfate is FeSO4·7H2O, the molar ratio of the soluble metal nitrate to the sulfate in the mixed solution is (2:1)-(1:2), the concentration of the soluble metal nitrate is 0.1-1.5 mg / mL, and the concentration of the divalent iron sulfate is 0.1-1.5 mg / mL.
[0037] In step S1, the SCE potential of the conductive substrate is -2 to -0.5 V, the constant potential deposition time is 50 to 400 s, and the constant potential deposition temperature is 10 to 50°C.
[0038] In step S2, the concentration of the KOH solution is 0.1 M, and the cyclic voltammetry potential is 1-4 V vs SCE.
[0039] In step S3, the LDH-O electrode is immersed for 30-90 minutes.
[0040] In step S3, in the mixed solution of hydroxylamine hydrochloride and Na2CO3, the concentrations of hydroxylamine hydrochloride and Na2CO3 are 80 mg / mL and 60 mg / mL respectively.
[0041] The present invention also provides an amidoxime-modified LDH-O@PA two-dimensional nanosheet array electrode material, which is prepared from the above-mentioned amidoxime-modified LDH-O@PA two-dimensional nanosheet array electrode material.
[0042] The present invention provides an amidoxime-modified LDH-O@PA two-dimensional nanosheet array electrode material for use in the fields of uranium extraction from seawater, nuclear wastewater treatment, hydrogen evolution reaction (HER) from water electrolysis, and oxygen evolution reaction (OER).
[0043] [Example 1]
[0044] Synthesis of Cobalt-Fe-Hydrotalcite Nanosheet Arrays Supported on Carbon Cloth:
[0045] a: The conductive carbon cloth was ultrasonically treated with anhydrous ethanol, acetone and deionized water for 10 min each to remove surface impurities, and then soaked in a standard potassium permanganate solution for 8 h;
[0046] b: Prepare 50 mL of a mixed salt solution of 0.15 mg / mL cobalt nitrate (Co(NO3)2) and 0.15 mg / mL ferrous sulfate (FeSO4) as an electrolyte solution;
[0047] c: In the electrolyte solution prepared in step b, a saturated calomel electrode was used as the reference electrode and a platinum wire was used as the counter electrode. Cobalt iron hydrotalcite (CoFe-LDH) nanosheet arrays were directly grown on nickel foam using a constant potential method. The electrochemical synthesis potential was set to -1 V, the synthesis time was 200 s, and the synthesis temperature was 25 ° C. The scanning electron microscope image of the prepared sample is shown in FIG. Figure 2 As shown, the prepared CoFe-LDH exhibits an obvious sheet-like array structure.
[0048] d: Prepare 0.1 mg / mL KOH solution, use saturated calomel electrode as reference electrode, Pt as counter electrode, and use cyclic voltammetry to synthesize LDH-O nanosheet arrays on CoFe-LDH synthesized in step c. The scanning electron microscope image of the sample is shown in Figure 3 As shown, after activation, the LDH-O sample maintains the array structure of the original nanosheets.
[0049] e: PAN and DMF were prepared in a ratio of 1:30, and the synthesized LDH-O was soaked in it for 30 minutes. After drying, it was bathed in a solution containing 80 mg / mL hydroxylamine hydrochloride and 60 mg / mL sodium carbonate at 70°C for 90 minutes. The LDH-O@PA nanosheet array electrode was rinsed with deionized water and dried. The scanning electron microscope image of the sample is shown in FIG. Figure 4 As shown in the figure, LDH-O still maintains a sheet-like structure after being coated with PAO, indicating that PAO is uniformly loaded on the nanosheets.
[0050] The synthesized LDH-O@PA nanosheet array electrode is used for the uranium extraction reaction from seawater. In this reaction, the LDH-O@PA nanosheet array electrode sheets are arranged in parallel, fixed 5-20cm below the liquid surface, and arranged using a flowing electrolytic cell or a floating platform device. The spacing between the electrode sheet and the counter electrode (platinum wire electrode) is adjusted to 1-2cm to optimize the electrolysis effect. Too large a spacing will increase resistance and energy consumption, while too small a spacing may cause a short circuit or electrode damage. The electrolysis equipment can be paired with a solar circuit board to achieve self-powered operation.
[0051] The scanning electron microscope image of the electrode material after adsorption is as follows: Figure 5 As shown, obvious uranium product deposition can be clearly seen on the surface of LDH-O@PA after adsorption.
[0052] [Example 2]
[0053] Synthesis of NiFe hydrotalcite nanosheet arrays supported on nickel foam:
[0054] a: The conductive substrate nickel foam was ultrasonically treated with anhydrous ethanol, acetone and deionized water for 10 min each to remove surface impurities;
[0055] b: Prepare 50 mL of a mixed salt solution of 1 mg / mL nickel nitrate (Ni(NO3)2) and 0.5 mg / mL ferrous sulfate (FeSO4) as an electrolyte solution;
[0056] c: In the electrolyte solution prepared in step a, a saturated calomel electrode was used as the reference electrode and a platinum wire was used as the counter electrode. The nickel-iron hydrotalcite nanosheet array was directly grown on the nickel foam by a constant potential method. The potential of the electrochemical synthesis was set to -0.9 V, the synthesis time was 200 s, and the synthesis temperature was 25°C.
[0057] d: Prepare 0.1 mg / mL KOH solution, use saturated calomel electrode as reference electrode, Pt as counter electrode, and use cyclic voltammetry to synthesize LDH-O on NiFe-LDH synthesized in step 2).
[0058] e: PAN and DMF were prepared in a ratio of 1:30, and the synthesized LDH-O was soaked in it for 30 minutes. After drying, it was bathed in a solution containing 80 mg / mL hydroxylamine hydrochloride and 60 mg / mL sodium carbonate at 70°C for 90 minutes, and then rinsed with deionized water and dried to synthesize LDH-O@PA.
[0059] [Example 3]
[0060] Synthesis of LiFeHydrotalcite Nanosheet Arrays:
[0061] a: The conductive substrate nickel foam was ultrasonically treated with anhydrous ethanol, acetone and deionized water for 10 min each to remove surface impurities;
[0062] b: Prepare 50 mL of a mixed salt solution of 0.5 mg / mL lithium nitrate (LiNO3) and 0.25 mg / mL ferrous sulfate (FeSO4) as an electrolyte solution;
[0063] c: In the electrolyte solution prepared in step a, a saturated calomel electrode was used as the reference electrode and a platinum wire was used as the counter electrode. The lithium iron hydrotalcite nanosheet array was directly grown on the nickel foam by a constant potential method. The potential of the electrochemical synthesis was set to -1.1 V, the synthesis time was 300 s, and the synthesis temperature was 25°C.
[0064] d: Prepare 0.1 mg / mL KOH solution, use saturated calomel electrode as reference electrode, Pt as counter electrode, and use cyclic voltammetry to synthesize LDH-O on LiFe-LDH synthesized in step 2).
[0065] e: PAN and DMF were prepared in a ratio of 1:30, and the synthesized LDH-O was soaked in it for 30 minutes. After drying, it was bathed in a solution containing 80 mg / mL hydroxylamine hydrochloride and 60 mg / mL sodium carbonate at 70°C for 90 minutes, and then rinsed with deionized water and dried to synthesize LDH-O@PAN.
[0066] Therefore, the preparation method and use of the amidoxime-modified LDH-O@PA two-dimensional nanosheet array electrode material provided by the present invention provide a new method for synthesizing nanosheet arrays by a one-step electrosynthesis method. The degree of oxygen exposure in the target compound can be adjusted by regulating the constant potential time and voltage, so that the product has a larger surface area and dispersion stability, and has a good synergistic adsorption effect on heavy metal ions.
[0067] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that they can still modify or replace the technical solution of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solution to deviate from the spirit and scope of the technical solution of the present invention.
Claims
1. A method for preparing an amidoxime-modified LDH-O@PA two-dimensional nanosheet array electrode material, characterized in that: The following steps are involved: S1. Construction of LDHs structured electrode: prepare a mixed solution of soluble metal nitrate and sulfate as an electrolyte solution, a saturated calomel electrode as a reference electrode, Pt as a counter electrode, select a clean conductive substrate for constant potential deposition, and directly grow an LDHs nanosheet array on the conductive substrate to obtain an LDHs structured electrode. The LDHs structured electrode is dried at 60° C. for 6 hours and then stored; S2. Construction of LDH-O electrode: Using cyclic voltammetry, the LDHs structured electrode is electrochemically activated in a KOH solution to obtain an LDH-O electrode; S3, LDH-O@PA two-dimensional nanosheet array electrode material construction: PAN and DMF were mixed and stirred at a mass ratio of 1:30 for 10-15h, the LDH-O electrode was soaked in it, and it was suspended and dried at 70°C; 25mL of a solution containing hydroxylamine hydrochloride and Na2CO3 was prepared with deionized water, the dried LDH-O electrode was soaked in it, and it was placed in a water bath at 70°C for 90min. After washing with deionized water, it was air-dried at 80°C in a drying oven to obtain the LDH-O@PA two-dimensional nanosheet array electrode material.
2. The method for preparing an amidoxime-modified LDH-O@PA two-dimensional nanosheet array electrode material according to claim 1, characterized in that: In step S1, the conductive substrate is selected from any one of nickel foam, ITO, FTO, nickel sheet, titanium sheet, copper mesh, carbon fiber cloth and transparent conductive cloth.
3. The method for preparing an amidoxime-modified LDH-O@PA two-dimensional nanosheet array electrode material according to claim 1, characterized in that: The cleaning method of the conductive substrate is as follows: ultrasonically treat the conductive substrate with anhydrous ethanol, acetone and deionized water for 10-20 minutes respectively to remove impurities on the surface, and then soak it in a standard potassium permanganate solution for 10 hours.
4. The method for preparing an amidoxime-modified LDH-O@PA two-dimensional nanosheet array electrode material according to claim 1, characterized in that: The soluble metal nitrate is selected from any one of Mg(NO3)2, Co(NO3)2, Ni(NO3)2, Ca(NO3)2, Cu(NO3)2, Fe(NO3)2, Mn(NO3)2, and LiNO3; the sulfate is FeSO4·7H2O, the molar ratio of the soluble metal nitrate to the sulfate in the mixed solution is (2:1)-(1:2), the concentration of the soluble metal nitrate is 0.1-1.5 mg / mL, and the concentration of the divalent iron sulfate is 0.1-1.5 mg / mL.
5. The method for preparing an amidoxime-modified LDH-O@PA two-dimensional nanosheet array electrode material according to claim 1, characterized in that: In step S1, the SCE potential of the conductive substrate is -2 to -0.5 V, the time of the constant potential deposition is 50 to 400 s, and the temperature of the constant potential deposition is 10 to 50°C.
6. The method for preparing an amidoxime-modified LDH-O@PA two-dimensional nanosheet array electrode material according to claim 1, characterized in that: In step S2, the concentration of the KOH solution is 0.1-2 M, and the cyclic voltammetry potential is 1-4 V vs SCE.
7. The method for preparing an amidoxime-modified LDH-O@PA two-dimensional nanosheet array electrode material according to claim 1, characterized in that: In step S3, the LDH-O electrode is immersed for 30-90 minutes.
8. The method for preparing an amidoxime-modified LDH-O@PA two-dimensional nanosheet array electrode material according to claim 1, characterized in that: In step S3, in the mixed solution of hydroxylamine hydrochloride and Na2CO3, the concentrations of hydroxylamine hydrochloride and Na2CO3 are 80 mg / mL and 60 mg / mL respectively.
9. An amidoxime-modified LDH-O@PA two-dimensional nanosheet array electrode material, characterized in that: The amidoxime-modified LDH-O@PA two-dimensional nanosheet array electrode material is prepared from the amidoxime-modified LDH-O@PA two-dimensional nanosheet array electrode material according to any one of claims 1 to 8.
10. The amidoxime-modified LDH-O@PA two-dimensional nanosheet array electrode material according to claim 9, characterized in that: An amidoxime-modified LDH-O@PA two-dimensional nanosheet array electrode material is used in the fields of uranium extraction from seawater and nuclear wastewater treatment.
Citation Information
Patent Citations
Method for preparing NiFe-LDH nanosheet efficient oxygen evolution catalyst through surface reconstruction
CN117187855A
High-performance catalyst as well as preparation method and application thereof
CN118086957A
Electrode material, production method and application thereof, and method for extracting uranium from seawater
CN118109877A
Method for preparing transition metal-based electrocatalytic water decomposition anode catalytic material and application of transition metal-based electrocatalytic water decomposition anode catalytic material
CN118186400A